Astronomical Chronology Framework of the Lingshui Formation (Oligocene) in the Northern South China Sea - Jianhao Liang; Yaning Wang; Shangfeng Zhang; Yubing Liang; Gaoyang Gong; Rui Han (Journal of Marine Science and Engineering)
This study has determined the period of sedimentation of the Lingshui Formation as the Oligocene (Rupelian-Chattian) through biostratigraphic data, including planktonic foraminifera zonation. The astronomical timescale framework for the Lingshui Formation was accurately constructed by integrating geophysical logging data and employing a multidisciplinary approach that includes time series analysis, cyclostratigraphy, astronomical dating, and Power Ratio Accumulation (PRA) methods. Sensitivity analysis of PRA has shown that natural gamma (GR) is the optimal paleoclimatic proxy, laying the foundation for subsequent analyses. The optimal sedimentation rate for the Lingshui Formation, determined by combining the coefficient of correlation (COCO) method with PRA analysis, is 5–5.4 cm/kyr. The duration of the Lingshui Formation was established at 5.02 Ma (28.52 Ma–23.5 Ma) based on time series analysis and astronomical tuning. The sediment noise model has revealed that the ~1.2 Myr obliquity modulation period has a significant impact on sea-level changes, further confirming the stratigraphic control of astronomical forcing on the sedimentation rate of the Lingshui Formation. This study establishes a high-precision astronomical timescale framework for the Lingshui Formation and provides a robust methodology, offering scientific basis for the research in astronomical chronostratigraphy and cycle stratigraphy, which has significant potential implications.